A case presentation and management of a hamartomatous vascular lesion of a patient with kaposi sarcoma - Erbalta, Rana; Cengiz, Beyza Nur; Coskunses, Fatih Mehmet; Ocbe, Melisa; Olgac, Vakur (Ikatan Radiologi Kedokteran Gigi Indonesia, 2025)
Objectives: Intraosseous vascular lesions of the mandible are uncommon and often difficult to diagnose. This report presents the clinical, radiographic, and histopathological findings of such a lesion in an elderly patient with a history of Kaposi sarcoma, emphasizing diagnostic challenges and management considerations. Case Report: A 73-year-old male with a medical history of Kaposi sarcoma was referred for evaluation of an edentulous mandible. Panoramic radiography and cone-beam computed tomography (CBCT) revealed a well-defined hypodense lesion adjacent to the mandibular canal, measuring 41 × 19 × 11 mm. The lesion demonstrated cortical thinning without expansion or perforation. An incisional biopsy revealed vascular lumens, and the final diagnosis was a hamartomatous vascular lesion. Considering the patient’s advanced age and medical condition, conservative management with regular clinical and radiographic follow-up was chosen. Conclusion: Although intraosseous vascular lesions of the mandible are rare, they should be included in the differential diagnosis of radiolucent jaw lesions. Radiographic and histopathological evaluations play a crucial role in diagnosis. In medically compromised or elderly patients, conservative management with close monitoring can be a suitable treatment option.